THE ROLE OF QUALITY MANAGEMENT IN INNOVATION PERFORMANCE IN STARTUPS: A LITERATURE REVIEW - Andreas Mahendro Kuncoro (JURNAL ILMU MANAJEMEN, 2021)
This paper provides insights in linking quality management practices and innovation performance in startups as it assists on how to enhance the startups innovativeness by engaging quality management practices. Innovation has been considered in building competitive advantage in organizations. The need to develop and improve its innovation performance requires understanding the antecedents of innovation. Quality management practices are often considered as the key drivers of innovation performance in organizations. Despite the importance of quality management practices and innovation performance, studies linking these concepts in startups are limited.